Bernini - Bacchi, Andrea 1959-; Coliva, Anna 1953-; Barberini, Maria Giulia; Desmas, Anne-Lise 1971-; Ficacci, Luigi 1954-; Levy, Evonne Anita 1961-; McPhee, Sarah 1960-; Petrucci, Francesco 1958-; Pierguidi, Stefano 1973-; Simonato, Lucia 1976-; Sparti, Donatella Livia (Officina Libraria, 2017)
Gianlorenzo Bernini (1598-1680), architect, painter, but above all sculptor, had a career that spanned almost three quarters of a century. He worked under six different popes and was instrumental in the ornamentation of Baroque Rome, from the colonnade of St. Peter to the fountains in piazza Navona and piazza di Spagna, from the many stunning sculptural groups in the churches and palaces of Rome to the dozens of 'speaking portraits', which depict cardinals, popes, kings and intellectuals of his time. The Galleria Borghese, home of many works by Bernini, including some of his world-famous groups such as Apollo and Daphne, The Rape of Proserpina and David, will host a major exhibition on the sculptures of this extraordinary artist. Exceptional in scope and scholarship, the catalogue analyses many different aspects of Bernini's output, focusing on the many innovations he introduced. It also devotes studies to the critical reception of Bernini and to his relationships with friends and patrons (a dictionary of these is included at the end of the book). Exhibition: Galleria Borghese, Rome, Italy (01.11.2017-04.02.2018)
Keywords: Bernini, Gian Lorenzo -- 1598-1680; Plastik; Ausstellungskatalog -- Galleria Borghese -- 01.11.2017-04.02.2018 -- Rom; Bildband